2019
DOI: 10.1186/s12879-019-4652-5
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage, spa types and antibiotic susceptibility profiles of Staphylococcus aureus from healthy children less than 5 years in Eastern Uganda

Abstract: BackgroundStaphylococcus aureus carriage is a known risk factor for staphylococcal disease. However, the carriage rates vary by country, demographic group and profession. This study aimed to determine the S. aureus carriage rate in children in Eastern Uganda, and identify S. aureus lineages that cause infection in Uganda.MethodsNasopharyngeal samples from 742 healthy children less than 5 years residing in the Iganga/Mayuge Health and Demographic Surveillance Site in Eastern Uganda were processed for isolation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
0
12
2
Order By: Relevance
“…aureus carriage to that found in an Ethiopian study in 2017 that reported a prevalence of 13% (52/400) among pre-school children [ 19 ]. On the other hand, the rate found in this study was a little lower than that of a Ugandan child population in the same age group with a carriage rate of 19.4% [ 20 ] or in a Ghanaian population where it was 21% [ 21 ]. After mass administration of azithromycin in the community, the prevalence of S .…”
Section: Discussioncontrasting
confidence: 80%
“…aureus carriage to that found in an Ethiopian study in 2017 that reported a prevalence of 13% (52/400) among pre-school children [ 19 ]. On the other hand, the rate found in this study was a little lower than that of a Ugandan child population in the same age group with a carriage rate of 19.4% [ 20 ] or in a Ghanaian population where it was 21% [ 21 ]. After mass administration of azithromycin in the community, the prevalence of S .…”
Section: Discussioncontrasting
confidence: 80%
“…Mupirocin resistance in Kenya as reported by the few studies ranged from 0% -18% in comparison with the continental pooled estimate of 14% (0% -49.6%) [40]. High level mupirocin resistance has recently been observed among carriage strains in Uganda [42].…”
Section: Antimicrobial Resistance Profiles Of S Aureusmentioning
confidence: 85%
“…In Uganda, t645, t4353, t355, t037 and t064 are the most common with t645 and t4353 appearing less frequently in Kenya [42]. Spa types t037 has been associated with HA-MRSA strains while t064 has been linked to CA-MRSA infections in Uganda [42]. Spa types t042 and t044 have been observed in Egypt and Algeria and were not reported in Kenya [8] whereas in Ghana, t355, t084, t10519 and t008 have been the preponderant strains [50].…”
Section: Molecular Characterization Of Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, MRSA isolates have a greater variety of virulence genes, among which the presence of pvl, tsst and sea stand out, and these are mainly associated with MRSA isolates with SCCmec-IV. [53][54][55][56] The frequency of pvl in MRSA varies from 9-30%; in Iran (9.7%), South Africa (14%), the US (26%), and China (30%). [50][51][52]55 In the current study, we found the pvl gene in four isolates (1.6%), all with SCCmec-IV.…”
Section: Discussionmentioning
confidence: 99%